Characterization of the therapeutic communication of nurses in a hospital of Ceará, Brazil - Patrícia de Lemos Negreiros; Mayara de Oliveira Fernandes; Kátia Nêyla de Freitas Macêdo-Costa; Grazielle Roberta Freitas da Silva (Universidad de Alicante, 2012)
Introduction: The communication between nurses and patients in the hospital environment excessively intervenes with the process of treatment of the health. From the moment that imperfections, these can be identified to improve the interaction and the assistance of nursing. Aims: To characterize the therapeutical communication between nurses and patients in the hospital environment according to estimated of Stefanelli. Material and Method: Study description with carried through quantitative boarding in a hospital of the state of the Ceará in julho/2007. The citizens of the study had been five nurses. Comment of 21 interactions established between nurses and patients was carried through. For the registers of the data a suitable instrument's Stefanelli was used daily of field. Results: The not-therapeutical's item had been gifts in the interactions of the majority of the nurses, occurring 32 times during the 21 interactions. Intent it the fact of that, the used item more was the use of professional jargon. The unidirectional communication occurred frequently. Conclusions: The nurses if communicate little of efficient and not directed form during the interactions that establish with the patients of the hospital.